2021
DOI: 10.5511/plantbiotechnology.21.0603a
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of rice OsLEA5 relieves the deterioration in seed quality caused by high-temperature stress

Abstract: Late embryogenesis abundant protein (LEA) genes are widely conserved in seed plant species and form a multigene family. While some LEAs are known to respond to environmental stresses, the function of many LEAs is unknown. OsLEA5 (Lea14A) interacts with a regulator of the endosperm storage production, FLO2, suggesting that OsLEA5 may be involved in endosperm quality control. RNAi knockdown line of OsLEA5 showed decreased seed weight. Transformant lines overexpressing OsLEA5 exhibited improved quality and seed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Two significant DEGs, Gh_D11G0978 and Gh_D10G0907 , were obtained by summarizing the annotation and function of the target genes and comparing the differential expression fold under salt stress and the control, and the homologous genes were found to be significantly salt tolerant in other species. The Gh_D11G0978 homolog LEA is involved in the regulation of embryonic development under osmotic stress and is found in a variety of crops including maize and wheat ( Jia et al., 2014 ; Miyazaki et al., 2021 ). Gh_D10G0907 , a GGPS family gene encoding glycerol-glucoside phosphate synthase that synthesizes glycerol-3-phosphate and adenosine diphosphate (ADP)-glucose into glycerol-glucoside phosphate, is a known salt-tolerant gene in algae and microorganisms ( Takashima et al., 2020 ; Klähn et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two significant DEGs, Gh_D11G0978 and Gh_D10G0907 , were obtained by summarizing the annotation and function of the target genes and comparing the differential expression fold under salt stress and the control, and the homologous genes were found to be significantly salt tolerant in other species. The Gh_D11G0978 homolog LEA is involved in the regulation of embryonic development under osmotic stress and is found in a variety of crops including maize and wheat ( Jia et al., 2014 ; Miyazaki et al., 2021 ). Gh_D10G0907 , a GGPS family gene encoding glycerol-glucoside phosphate synthase that synthesizes glycerol-3-phosphate and adenosine diphosphate (ADP)-glucose into glycerol-glucoside phosphate, is a known salt-tolerant gene in algae and microorganisms ( Takashima et al., 2020 ; Klähn et al., 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of LEA14 in sweet potato embryonic healing tissues increases tolerance to salt stress through enhanced lignification ( Park et al., 2010 ). In addition, OsLEA5 in rice enhances resistance to a variety of abiotic stresses ( Miyazaki et al., 2021 ). Overall, LEA proteins are closely associated with resistance to a variety of abiotic stresses and can increase plant resistance to drought and salt tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…Late embryogenesis abundant proteins are instrumental in seed development in higher plants, and its expression can be considered as a clear indication of seed maturation [13,14]. Some LEA proteins are crucial for seed longevity, desiccation tolerance, and endosperm quality control [15][16][17][18]. For example, the weight, size, and fatty acid content of Arabidopsis seeds overexpressing LuLEA1 are reduced [19].…”
mentioning
confidence: 99%
“…LEA proteins act as osmoprotectants, membrane stabilizers, antioxidants and molecular chaperones, indicating their response to drought stress (Bremer et al, 2017; Candat et al, 2014; Saha et al, 2016). The overexpression of LEA5 (Miyazaki et al, 2021) and LEA3‐1 (Xiao et al, 2007) in rice has been shown to enhance the resilience to drought compared to the wild type. In Arabidopsis , the efficacy of LEA overexpression in regulating drought stress involves several factors: improved photosynthesis rate, increased sucrose deposition, reduced lipid oxidation, minimized membrane deformation and upregulated fatty acid synthesis (Liang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%